2018
DOI: 10.1007/s10865-018-9964-1
|View full text |Cite
|
Sign up to set email alerts
|

Can the artificial intelligence technique of reinforcement learning use continuously-monitored digital data to optimize treatment for weight loss?

Abstract: Behavioral weight loss (WL) trials show that, on average, participants regain lost weight unless provided long-term, intensive-and thus costly-intervention. Optimization solutions have shown mixed success. The artificial intelligence principle of "reinforcement learning" (RL) offers a new and more sophisticated form of optimization in which the intensity of each individual's intervention is continuously adjusted depending on patterns of response. In this pilot, we evaluated the feasibility and acceptability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
0
47
0
1
Order By: Relevance
“…This could be attributed to the personalisation of goals that were coherent with each users' lifestyle habits based on the information retrieved from their calendar apps (indicates availability for exercise) and health app (indicates activity patterns) (26) . Weight loss outcomes ranged from an average of 2•4 -4•7 % (29,(48)(49)(50)106) of which only two were statistically significant (P < 0•05) (26,50) . Three studies reported the use of Bluetooth enabled weighing machines that synchronise weight data to the users' phone apps, while the rest used manually-input weight.…”
Section: Real-time Analytics and Personalised Micro-interventions: Self-controlmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to the personalisation of goals that were coherent with each users' lifestyle habits based on the information retrieved from their calendar apps (indicates availability for exercise) and health app (indicates activity patterns) (26) . Weight loss outcomes ranged from an average of 2•4 -4•7 % (29,(48)(49)(50)106) of which only two were statistically significant (P < 0•05) (26,50) . Three studies reported the use of Bluetooth enabled weighing machines that synchronise weight data to the users' phone apps, while the rest used manually-input weight.…”
Section: Real-time Analytics and Personalised Micro-interventions: Self-controlmentioning
confidence: 99%
“…Three studies (26,53,54) focused on only improving physical activity, four studies focused on only improving dietary behaviours (48)(49)(50)106) and three studies (29,51,52) focused on both. All five studies (29,48,49,50,53) on dietary lapse prevention reported percentage increases in dietary adherence, but only one study reported statistically significant results (P < 0•05), suggesting mixed findings (50) . Two of the three studies on preventing exercise lapses reported significant (P < 0•05) increases in step count and metabolic equivalent task (26,53) .…”
Section: Real-time Analytics and Personalised Micro-interventions: Self-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Such techniques have been used for educational purposes. For instance, [28] created a decision-making algorithm to optimize a reinforcement learning system for a weight loss intervention program using pre-classified data from Fitbit sensors, together with intervention responses. [29] created a gamified intervention to motivate children to increase every-day physical activity where Support Vector Machine and Random Forests (RF) data mining techniques were applied to smartphone accelerometer data in order to (i) classify children's PA into activities (sitting, standing, walking, jogging, walking upstairs, walking downstairs and intense physical activity) and (ii) calculate a score based on the amount of time spent in these activities.…”
Section: B Supervised Techniquesmentioning
confidence: 99%
“…Alternatively a program that incorporates text messages which are supplemented with additional telephone support for emotional and social well-being may address this deficit and may be more appropriate extended contact for some participants (Singleton et al, 2019, Gell et al, 2019b, Job et al, 2017b. Furthermore, with recent developments, this support may be feasible through triaging levels of intervention intensity via artificial intelligence , Forman et al, 2019 or supplementing with chatbots to support skill development for psychological health (Greer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%